Pemanfaatan Kulit Ari Kelapa sebagai Alternatif Bahan Pakan untuk Ikan Nila (Oreochromis niloticus) - Sukarman Sukarman; Firdaus Ramadhan (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2015)
Feed is one of the most important things in aquaculture. More than 50% cost productiondecided by feed. The increase of artificial feed price affected by raw material price rising could troubled the farmers and cultivator. Coconut husk as waste in traditional markets. This research purpose to know the utilization of coconut husk as alternative feed material. This research used experiment method composed of one control and three treatmenteach of it with three repetitive. The treatment composition with 5%, 10%, and 15% coconut husk flour. The observed parameter in this research is survival rate, weight absolute, specific growth rate, conversion feed, and water quality. The obtained result is the feed with 15% coconut husk flour formulation had the best result compared from control with survival rate 100 ± 0%, weight absolute 11,75 ± 1,46 gram, specific growth rate 2,89 ± 0,41% and feed conversion ratio 1,62 ± 0,16 without the alteration of water quality. Coconut husk flour can be used as alternative feed material with 15% in formulation.